THE LEGITIMACY OF THE REGISTERED MAIL COURT SUMMON AND ITS CHALLENGES TO THE PRINCIPLE OF CONTANTE JUSTITIE IN THE SUNGAI PENUH RELIGIOUS COURT - Rizqi Aulia Muslim; Abdul Rachmad Budiono; Mohammad Hamidi Masykur (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Summoning hearings by registered mail is a new instrument in the e-Court system designed to strengthen the principle of contante justitie as a fundamental principle of simple, fast, and low-cost justice. This study aims to analyze the basis of the legitimacy of summoning a trial through a registered letter according to positive law and examine the challenges of its implementation in practice in the Sungai Penuh Religious Court. Using a socio-legal approach, this study integrates normative analysis of PERMA Number 7 of 2022, SEMA Number 1 of 2023, and HIR/RBg provisions with empirical findings obtained through observation and interviews. The results of the study show that although normatively recorded letters have formal legitimacy as a valid and appropriate summons, their effectiveness in the field has not fully supported the fulfillment of the principle of contante justitie. Various obstacles are still found, including delays in delivery, untimely receipts, high return rates, low understanding of postal officers on procedural legal procedures, and the defendant's attendance rate, which is only in the range of 35-36 percent. This situation causes a distortion between normative and functional legitimacy in the practice of summoning hearings. This research highlights the importance of reinforcement of operational standards, improvement of the capability of PT Pos Indonesia officers, and reconstruction of legally feasible standards in the form of electronic summons for the fulfillment of the principle of continual justice in the enactment of modern justice.